A Compact Dual-Band MIMO Antenna for Sub-6 GHz 5G Terminals - Dong, Guiting; Huang, Jianlin; Lin, Simin; Chen, Zhizhou; Liu, Gui (Journal of Electromagnetic Engineering and Science, 2022)
In this paper, a dual-band multiple-input-multiple-output (MIMO) antenna is proposed for fifth-generation (5G) wireless communication terminals. The measured -10 dB impedance bandwidths of 380 MHz (3.34–3.72 GHz) and 560 MHz (4.57–5.13 GHz) can cover the 3.4–3.6 GHz and 4.8–5 GHz 5G bands. The single antenna element of this proposed MIMO is composed of an F-shaped feed strip and an inverted L-shaped radiation strip. A defected ground structure is employed to obtain a good isolation performance, whereby the measured isolation between the antenna elements is observed to be larger than 23 dB. The measured total radiation efficiencies at 3.5 GHz and 4.9 GHz are 76.65% and 71.93%, respectively. Besides, the calculated envelope correlation coefficients (ECC) are less than 0.00125 and 0.01164 at the low-frequency and high-frequency bands, respectively. Furthermore, the specific absorption ratio (SAR) analysis of the antenna verifies that it qualifies for 5G terminals.